Influence of maximal strength performance in front squat and deadlift on linear sprint and jump performance in male youth elite basketball players - Warneke, K.; Keiner, M.; Schiemann, S.; Lohmann, L.; Wirth, K. (German Journal of Exercise and Sport Research, 2023)
Background: Strength and speed are two major factors that determine performance in basketball players especially sprinting, jumping and change of direction. This study examined relationships of maximal strength in the front squat and the deadlift with basketball-specific sprint and jump performance tests that are commonly used in test batteries of athletic diagnostics. Materials and methods: In all, 42 youth male elite basketball players (age: 14.7± 2.4 years, age range: 13-18 years, height: 179.1± 15.3cm, weight: 69.8± 19.2kg) volunteered to take part in the present study. The one repetition maximum (1RM) in the front squat and deadlift were used to determine maximum strength. Countermovement jump (CMJ) and standing long jump were evaluated to determine jump performance and 5, 10, and 20m linear sprint as well as agility T-test were performed to determine sprint performance. Pearson correlation analysis was used to assess the relationships between strength and jump and sprint performance. Results: Strong positive correlations were found between maximal strength and jump heights (r= 0.85-0.91, p< 0.001) and strong negative correlations were determined between maximal strength and measured sprint times r= (-0.71 to -0.85, p< 0.001). Conclusion: The measured maximal strength in the front squat and deadlift seem to be good predictors for basketball-specific jump and sprint performance. From this, it seems to be beneficial to include training of maximal strength via front squat and deadlift into training routines as well as performance diagnostics.